Evidence Based Classroom Management Practices : An Analysis Through Kano’s Model - Bawa, Pardeep (Indian Journal of Marketing, 2017)
Managing a classroom is much more difficult than it seems. Often, it is mistaken as only creating discipline in the class, but it is about engaging students in a meaningful and effective learning environment through discipline. According to LaCaze, McCormick, and Meyer (2012), creation and maintenance of a productive classroom environment is what teaching competency primarily depends upon. Those teaching practices should be adopted/used that can make students learn effectively. In other words, teaching practices should be supported by evidence that they are effective. There are two major challenges here. One is to identify effective classroom management practices backed by evidence. Second is to categorize them in terms of their contribution towards learning. Categorization helps in chalking out a plan to effectively manage a classroom (Yadav, Jain, Shukla, Avikal, & Mishra, 2013). This paper identified effective classroom management practices through a thorough literature review followed by categorization of different classroom management practices’ contribution in learning through Kano’s model, which provides a two-dimensional view of service quality wherein components of service quality can be categorized in terms of contribution towards customer satisfaction, which is very significant as students do assess service quality (Gupta, 2016). This paper would help academia in improving learning of students in a typical business school classroom environment through categorization of evidence based classroom management practices.